YOUR FUTURE AT RISK – ARE YOU PREPARED?. Issue 2 (July 2016) - deLamare, Michael; Walker, Loren Mark; Juhasz, John
ABSTRACT: Critical infrastructures are highly vulnerable to a variety of threat scenarios. Three specific threats are known to endanger critical infrastructure so pervasively that a large‐scale incident could make vital services unavailable for a period of a month or more — possibly much more. These threats include Electro‐Magnetic Pulse (EMP) weapons, Geo‐Magnetic Disturbances (GMD) and cyber incidents in information technology and industrial control systems. These threats, sometimes referred to as the "triple threats" can cause damage from regional to continental or even global scales such that obtaining help from neighboring regions is unlikely since all neighboring regions may be equally and significantly damaged. The seriousness of the threats are so severe, as the EMP Commission reported to the US Congress that power outages could last a year or more, resulting in substantial loss of life. Let that warning sink in for a moment. Agile system principles evolved via INCOSE methods and other organizations are considered instrumental in planning for resiliency and recovery from catastrophic events. Agile systems use multiple independent encapsulated modules as the principle system components. Each module is highly cohesive internally, loosely coupled with the other modules, yet they cooperate toward a shared common purpose. These principles would be applicable to social units of organization during a recovery process, and are considered a vital step in contingency pre‐planning for such threat scenarios. This article provides background on the triple threats and explores the application of specific core agile principles applied to social organizing for achieving resiliency.